A Comprehensive Analysis of the Colonic Flora Diversity, Short Chain Fatty Acid Metabolism, Transcripts, and Biochemical Indexes in Heat-Stressed Pigs - Hu, Canying; Niu, Xueting; Chen, Shengwei; Wen, Jiaying; Bao, Minglong; Mohyuddin, Sahar Ghulam; Yong, Yanhong; Liu, Xiaoxi; Wu, Lianyun; Yu, Zhichao; Ma, Xinbin; Ju, Xianghong (Frontiers in Immunology, 2021)
Heat stressed pigs show typical characteristics of inflammatory bowel disease (IBD). However, little is known about the pathogenesis of heat stress (HS)-induced IBD in pigs. In this study, we determined the effects of HS on colon morphology, intestinal microbiota diversity, transcriptome genes (transcripts), and short chain fatty acids (SCFAs) metabolism in pigs. In addition, the correlation among these parameters was analyzed by weighted gene co-expression network analysis. Results showed that the liver and kidney functions related to blood biochemical indexes were partially changed in pigs under HS. Furthermore, the levels of diamine oxidase and D-lactic acid were significantly increased, whereas the levels of secretory immunoglobulin A were decreased. The integrity of colonic tissue was damaged under HS, as bleeding, lymphatic infiltration, and villi injury were observed. The concentrations of SCFAs in the colon, such as acetic acid and butyric acid, were decreased significantly (P < 0.05). In addition, the diversity and structure of colonic microorganisms changed dramatically, such as decrease in Streptococcaceae, Lactobacillales, and Megasphaera and increase in Clostridium_sensu_stricto_1. These changes were associated with changes in the concentration of SCFAs and biochemical indexes above mentioned. Differentially expressed genes were enriched in the nucleotide-binding oligomerization domain-like receptor signalling pathway, Th17 cell differentiation, and IBD pathway, which were also associated with the changes in SCFAs. Thus, the structure, diversity, and metabolite levels of intestinal microorganisms in heat stressed pigs changed significantly, leading to the activation of immune response and inflammatory signal pathways and causing abnormal physiological and biochemical indexes and intestinal mucosal damage. These results highlight the correlation between intestinal microbiota, SCFAs, and immune response and their role in the pathogenesis of stress induced IBD therapy.